Exploring the Role of Facade Materials and Natural Ventilation on Thermal Comfort and Energy Efficiency in Office Buildings across Diverse Climate Zones - Nidhi Maurya (Journal of Alternative and Renewable Energy Sources, 2025)
The design of office buildings significantly impacts thermal comfort and energy efficiency, both critical factors for sustainable development in the built environment. This study explores the interplay between façade materials and natural ventilation in optimizing energy performance and occupant comfort across diverse climate zones. Recognizing the growing need for environmentally conscious building practices, it evaluates various façade materials, including double glazing, clay, bamboo, and green roofs, and their role in indoor temperature regulation and energy demand. The research highlights the importance of natural ventilation, especially in temperate climates, by analyzing airflow management and its contribution to thermal comfort and energy savings. Advanced glazing technologies, such as triple-glazed windows, are examined through case studies to assess their effectiveness in extreme climatic conditions. The methodology integrates literature reviews, case studies, and occupant surveys, providing a holistic understanding of material properties, ventilation strategies, and user feedback. Findings from this study consolidate evidence from academic databases, energy performance reports, and occupant insights to offer practical recommendations for material selection and ventilation strategies. By addressing the challenges of energy efficiency and occupant comfort, this research aims to guide architects and building managers in implementing sustainable solutions tailored to varying environmental conditions.